Politik Luar Negeri Pemerintahan Susilo Bambang Yudhoyono terhadap Eropa - Rahman, Agus R (Jurnal Penelitian Politik, 2005)
The airns ofthis paper is to explain the important ofEurope in President Susilo Bambang Yudhoyono foreign policy. The approach ofthis research is based on individual factor as determinant factor that effect Indonesian foreign policy which is conseptualized infour components. The result ofthis research is Europe is not the main priority in Indonesian foreign policy under President SBY because Europe does not have clear position due to their several domestic problems and because the main priority in Indonesian foreign policy is based on two pillars of regionalism, such as ASEAN and APEC.